Reviews and Propose Model for the System Dynamics in Contemporary Tendencies of Third-Party Logistics towards Business Performance in Malaysia and Thailand - et.al, Awoyemi Adebare Omotayo (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present Third Party Logistics (3PL) service providers in Malaysia and Thailand are expending their effectiveness and efficiency in several spheres from contemporary logistics services offers towards the series of value-added services to their customers. There is a need to forecast their key performance indicators growth using a systematic approach in resource management, as their quality indicators. Hence, this paper discovers on the current propensities of 3PLs service providers in respect of issues connected with their performance, resources and quality to establish on the 3PLs indicators of resources, quality and processes. It is also sought to develop a model of systematic dynamics for internal resources and company processes optimization based on the best practices. The methodology of the research is based on literature reviews which focusing on the performance measurement, quality and resources of 3PL. Using a System Dynamics, a model of optimization and management of 3PL, the internal processes and resources were developed. This model comprises of Nine (9) segmentations, which are operations, commercial activities, administration, personnel management, procurement, quality management, Resources, Performance Measurement and Financial models. The model is indicating all areas of activities of 3PL service providers. This study proposes a new model for Third-party Logistics (3PL) performance indicators for future guidelines in related industry.